Dietary Level of the Omega-3 Fatty Acids EPA and DHA Influence the Flesh Pigmentation in Atlantic Salmon - T. Ytrestøyl; M. Bou; C. Dimitriou; G. M. Berge; T.-K. Østbye; B. Ruyter (Aquaculture Nutrition)
Atlantic salmon with a start weight of 53 g were fed diets with different levels of EPA and DHA or a diet with 1 : 1 EPA+DHA (0%, 1.0%, and 2.0% of the diet). At 400 g, all fish groups were mixed and equally distributed in new tanks and fed three diets with 0.2%, 1.0%, or 1.7% of EPA+DHA. At 1200 g, the fish were transferred to seawater pens where they were fed the same three diets until they reached a slaughter size of 3.5 kg. The fillet concentration of astaxanthin and its metabolite idoxanthin was analysed before transfer to seawater pens at 1200 g and at slaughter. The fatty acid composition in the fillet was also analysed at the same time points. Salmon fed low levels of EPA and DHA had lower fillet astaxanthin concentration and higher metabolic conversion of astaxanthin to idoxanthin compared to salmon fed higher dietary levels of EPA and/or DHA. DHA had a more positive effect on fillet astaxanthin concentrations than EPA. There were positive correlations between fillet DHA, EPA, sum N-3 fatty acids, and fillet astaxanthin concentration. A negative correlation was found between the concentration of N-6 fatty acids in the fillet and the astaxanthin concentration.